Status Kepemilikan Tanah Adat Di Bali Yang Diakui Sebagai Tanah Milik Pribadi - Apriyani, Putu Indi (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 3 No 2 (2018)DO - 10.24843/AC.2018.v03.i02.p10, 2018)
Based on the provisions of Article 9 paragraph (5) Regional Regulation of Bali Province Number 3 of 2001 concerning Pakraman Village juncto Regional Regulation of Bali Province Number 3 of 2003 concerning changes in Bali Provincial Regulation Number 3 of 2001 concerning Pakraman Village, it has been clearly determined that village land and or land owned by Pakraman village cannot be certified in private name. Sociologically, there is still a gap between the regulation of village land (das sollen) and its implementation regarding the ownership status of village land (das sein). From the description of the previous background, there are formulations of the problem, among others: (1) What are the factors that cause the number of customary lands in Bali to be recognized as private property? and (2) How are efforts to reduce customary land in Bali to private property? The purpose of this study was to analyze the factors that caused customary land in Bali to be private land. The method used in this paper is an empirical legal research method by examining primary data and secondary data with library observation and literature techniques. The results of this study indicate that: (1) the lack of legal awareness of indigenous peoples to comply with legal norms, then the lack of community support in the implementation of legal norms and intentions in ignoring legal norms. And (2) certifying the customary land by making Pakraman village as its legal subject, considering the Appointment of Pakraman Village in Bali Province as the Subject of Land-based Joint Communal Law based on Minister of Agrarian and Spatial Planning National Land Agency Number 276 / KEP-19.2 / X / 2017.